PENILAIAN RISIKO KEBAKARAN PADA PROSES PENGGILINGAN BATU BARA DI INDUSTRI SEMEN - Mochamad Yusuf Santoso; Adianto; Alek Aribowo (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Risk assessment is an important and strategic response to ensuring the health and safety of workers and in maintaining a quality workforce due to the industrial network complexity growing and the rapid growth of engineering in cement factories. The usage of coal in the cement industry is one of the hazards which can cause the emergence of safety risks. The fire risk assessment was prompted by a potential fire and even an explosion during the coal milling procedure at one of the cement facilities in East Java. This fire risk was evaluated using the National Fire Protection Association (NFPA) 551 qualitative checklist approach. The NFPA 51B clause regarding hot work is referenced when creating the checklist. The analysis’s findings revealed that 96.67% of the clauses had been satisfied. Companies must be aware of coal dust originating from supporting equipment and should install a fire early warning system in the coal mill area. According to the specifications of the Indonesian National Standard (SNI), the suggested early warning system is offered in the form of heat and carbon monoxide detectors put on the walls of the coal mill and integrated with alarms on each floor where the coal mill is located.